Pendampingan Pengelolaan UMKM Bakpia Tunas Ngrombo Berbasis Mentoring Kelompok - Agus Abdurrahman; Fuad Hasyim (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The management assistance Micro, Small, and Medium Enterprises (MSMEs) based on group mentoring has proven effective in enhancing the performance and sustainability of MSMEs. This study aims to analyze the impact of the group mentoring program on Bakpia Tunas Ngrombo MSMEs. The method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results show that group mentoring can improve managerial capacity, market access, and digital literacy of MSME actors. Additionally, this mentoring program can also enhance product competitiveness and expand the business network of Bakpia Tunas Ngrombo MSMEs.